2023
DOI: 10.3324/haematol.2023.283251
|View full text |Cite
|
Sign up to set email alerts
|

Elotuzumab plus pomalidomide and dexamethasone in relapsed/refractory multiple myeloma: a multicenter, retrospective real-world experience with 200 cases outside of controlled clinical trials

Abstract: In the ELOQUENT-3 trial, the combination of elotuzumab, pomalidomide and dexamethasone (EloPd) proved a superior clinical benefit over Pd with a manageable toxicity profile, leading to its approval in relapsed/refractory multiple myeloma (RRMM), who had received at least two prior therapies, including lenalidomide and a proteasome inhibitor (PI). We report here a real-world experience of 200 RRMMs treated with EloPd in 35 Italian centers outside of clinical trials. In our dataset, the median number of prior li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 26 publications
(52 reference statements)
3
8
0
Order By: Relevance
“…Consequently, these results indicate that elotuzumab should be used prior to anti-CD38 antibody administration. This result is consistent with the findings from previously reported univariate analyses [14].…”
Section: Discussionsupporting
confidence: 94%
“…Consequently, these results indicate that elotuzumab should be used prior to anti-CD38 antibody administration. This result is consistent with the findings from previously reported univariate analyses [14].…”
Section: Discussionsupporting
confidence: 94%
“…The extended follow-up duration of our cohort of patients treated with EloPd in a real-life setting corroborates the findings of our previous analysis. 18 The median PFS of 7.5 months, ascertained in the current study, aligns consistently with our previous investigation, 18 but is inferior to that observed in the registered trial ELOQUENT-3 (10.3 months). 17 Likewise, OS remained inferior to that reported in the original trial (19.2 months versus 29.8 months), 17 slightly longer than OS emerged from our previous analysis.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, many studies worldwide have already shown how several previous lines of therapy negatively impact survival in those settings of patients 2–4 …”
Section: Future Perspectivementioning
confidence: 99%
“…Treatment of multiple myeloma (MM) drastically improved in recent decades, due to the introduction of novel drugs into clinical practice, such as proteasome inhibitors (PIs), immunomodulatory drugs (IMiDs), and monoclonal antibodies (MoAbs), which have extended progression‐free survival (PFS) and overall survival (OS) of MM patients 1–19 . Given the disease's natural history, which is marked by alternating periods of remission and relapses, the majority of patients are doomed to be refractory to those agents.…”
Section: Introductionmentioning
confidence: 99%